Review Kinerja Keuangan Sebelum dan Sesudah Merger dan Akusisi - Yumna Sekar Utami; Rosita Putri Cahyawati; Ahmad Iqbal Suyudi; Yafet Yulianto; Lucky Monic Sabatini (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
This review is intended to explain the dissimilarity of financial performance before and after mergers and acquisitions in developing countries and Indonesia. Liquidity, capital, profitability, and stock performance are financial ratios used when measuring a company's financial performance. Theoretically, explanations that support mergers and acquisitions are described, then critically discuss empirical studies of previous research in the previous literature. From the existing literature, it is known that there are different results on the financial performance of companies in developing countries including Indonesia after mergers and acquisitions are carried out.